Comparison of Behavior-Related Features in the MMSE Sentence in Behavioral Variant Frontotemporal Dementia and Alzheimer’s Disease - Ruiz-Garcia, Ramiro; Yu, Soojung; Richardson, Lauryn; Roberts, Angela; Pasternak, Stephen; Stewart, Chloe; Finger, Elizabeth (Frontiers in Aging Neuroscience, 2021)
Background: Despite the ubiquity of cognitive assessments using the MMSE, there has been little investigation of currently unscored features of the MMSE sentence item relevant to behavior and language in patients with behavioral variant Frontotemporal Dementia (bvFTD) and Alzheimer’s disease (AD). Objective: To describe and compare the unscored content and grammar elements of the MMSE sentence item in patients with bvFTD and AD. Methods: Categorization of predefined content and grammar elements of the MMSE sentence was performed by two blinded raters in patients with bvFTD (n = 74) and AD (n = 84). Chi-square and ANCOVAs were conducted to identify differences between the diagnostic groups. A multinomial logistic regression analysis was conducted to determine whether these features aid in the prediction of diagnosis of bvFTD or AD. Results: A higher proportion of patients with bvFTD wrote sentences addressed to the examiner (22.7% vs. 4.7%, X2 = 11.272, p = 0.001) and about interpersonal relationships (35.3% vs. 16.0%, X2 = 10.139, p = 0.017) in comparison to those with AD. The number of words written was lower in patients with AD and was positively correlated with lower total MMSE scores in AD but not in bvFTD (AD: r = 0.370, p < 0.001; FTD: r = 0.209, p = 0.07). Assessment of the MMSE sentence content and grammar variables did not add to the prediction bvFTD or AD diagnosis beyond the variance explained by age and total MoCA score. Conclusions: Patients with bvFTD and AD showed differences in aspects of the content of the written MMSE sentence item, though these differences did not aid in the diagnosis prediction.